Nutritional properties of wild and fattening mud crab (Scylla serrata) in the south-eastern district of Bangladesh - Islam, Tajimul; Saha, Debasish; Bhowmik, Shuva; Nordin, Noordiana; Islam, Shabiha; Ujjaman Nur, As-Ad; Begum, Mohajira (Elsevier BV, 2022)
Mud crab (Scylla serrata) is one of the most important crustacean species in Bangladesh due to its high economic value. Crab fattening is widely practiced in the country to meet export demand while the supply for domestic consumption is mainly dependent on wild sources. This work reported for the first time a comparative evaluation of the nutritional properties of wild and fattening mud crabs. For this purpose, the proximate compositions were determined in terms of total contents of protein, moisture, ash, lipid, and minerals. Female fattening mud crabs had the highest levels of protein (17.07 ± 1.52%) and moisture (76.95 ± 1.39%) content, while the highest percentages of ash (4.9 ± 1.03%) were detected in male fattening mud crabs. Male fattening mud crabs also contained high amounts of minerals, especially calcium (1199.71 ± 343.43 mg/100g) and iron (14.21 ± 1.28 mg/100g). Male and female wild crabs showed the highest levels of magnesium and phosphorus, respectively. Additionally, the calculated percentage of recommended nutrient intake (RNI) value revealed that mud crab contributes 4.4–59.99%, 6.6–53.98%, and 7.33–54.53% for infants, adults, pregnant and lactating women, respectively. The present study indicates that mud crab had a balanced nutritional composition that would be nutrient-rich excellent diet for consumers.